PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA TOKO IKAN HIAS AQUATICXO AROWANA PONDOK AREN - Fahreza Budi Ramdhan; Nani (Journal of Research and Publication Innovation, 2025)
This research aims to determine the variable "The Influence of Service Quality and Location on Consumer Satisfaction at the Aquaticxo Arowana Pondok Aren Shop". The research method used is associative research with a quantitative approach. The population in this study was consumers of the Aquaticxo Arowana Pondok Aren Ornamental Fish Shop. The sample in this research was 93 respondents. Sampling used the Slovin formula. The data collection methods used were questionnaires, literature study and observation. Data analysis methods used include: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Multiple Linear Regression, t Test (Partial), F Test (Simultaneous), Correlation Coefficient (R), Determination Coefficient (R2) and Hypothesis Testing with the help of software SPSS 26. The research results from the t test show that the significance value of the 2 independent variables is more than 0.05, thus it can be concluded that partially both Service Quality and Location have an influence on Consumer Satisfaction. Meanwhile, from the results of the F test (simultaneous), a significance value of 0.000 (0.000 < 0.05) was obtained and an Fcount value of 32,640, which means Fcount is greater than Ftable (32,640 > 3.098), which means that the Service Quality and Location variables influence Consumer Satisfaction. From the results of the correlation coefficient test, an R value of 0.648 was obtained, where the Service Quality and Location variables have a very strong level of correlation with Consumer Satisfaction. And from the results of the coefficient of determination test (R2), the R square value is 0.420, which means that the influence of the Service Quality and Location variables on Consumer Satisfaction in this research is 42.0% while the remaining 58.0% is influenced by other variables not examined in the research. This.